The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1111/epp.12131
|View full text |Cite
|
Sign up to set email alerts
|

Is terrestrial plant import from East Asia into countries in the EPPO region a potential pathway for new emerging invasive alien plants?

Abstract: Pathway analysis represents an effective means of identifying emerging invasive alien species. For plants, a significant number of invasions have been caused by plant species originally voluntary introduced as ornamentals. The pathway analysis for terrestrial ornamental plants imported from East Asia has been undertaken to provide information on the imports and to identify emerging terrestrial invasive alien plants. Data for terrestrial ornamental plants imported from East

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…Novelty can produce premiums for the industry, so there is a constant pressure for breeders to produce new plant cultivars (Drew et al 2010). Plant characteristics desired by the industry include ease of propagation, stress tolerance, large flowers, long blooming season and easy care (van Valkenburg et al 2014). Analysis of the trade history showed that only 12-20% of the new genus-origin trade flows developed in a regular trade flow.…”
Section: Discussionmentioning
confidence: 99%
“…Novelty can produce premiums for the industry, so there is a constant pressure for breeders to produce new plant cultivars (Drew et al 2010). Plant characteristics desired by the industry include ease of propagation, stress tolerance, large flowers, long blooming season and easy care (van Valkenburg et al 2014). Analysis of the trade history showed that only 12-20% of the new genus-origin trade flows developed in a regular trade flow.…”
Section: Discussionmentioning
confidence: 99%
“…The plant has been widely planted and has subsequently become naturalized in many countries. It is currently known from at least 22 countries, including Argentina (Urcelay et al 2019); Australia (Moreschi et al 2019); Brazil (Guix 2007); Canada, Columbia, England, and France (de Villalobos et al 2010); the French Polynesian Islands and Hawaii (GBIF 2019); Italy, Japan, Mexico, New Zealand, Portugal, and Russia (GBIF 2019;Van Valkenburg et al 2014); South Africa (Henderson 2007); Spain and the United States (Cadic 1983; Andreu and Vilà 2011); Germany (Brändle and Brandl 2012); Lesotho (Kobisi et al 2019); and Swaziland (Henderson 2007). However, there is generally sparse knowledge on the distribution and invasive status of P. angustifolia globally.…”
Section: Geographic Descriptionmentioning
confidence: 99%
“…Minthogy a fajok propagulumai számára áthatolhatatlan barrierek az urbánus és szuburbán területeken gyakorlatilag nem léteznek, az egymással összeköttetésben lévő magánkertek az egyik legnagyobb, a kutatók számára azonban az egyik legnehezebben hozzáférhető élőhely-rendszert alkotják az emberi településeken (GASTON et al 2005). A lakosság, dísznövény preferenciája, valamint a dísznövény-és termesztő közeg (földlabda, virágföld) kereskedelem miatt, direkt és indirekt módon, jelentékeny mértékben járul hozzá egyes idegenhonos növényfajok elterjesztéséhez és meghonosodásához (DEHNEN-SCHMUTZ et al 2007a,b, KNAPP et al 2010, VAN VALKENBURG et al 2014, CUBINO et al 2015, PERGL et al 2016, ČEPLOVÁ et al 2017, CSIKY et al 2018, WIRTH 2018.…”
Section: Kitekintésunclassified